Mechanotransduction of Strain Regulates an Invasive Phenotype in Newly Transformed Epithelial Cells - Chagnon-Lessard, Sophie; Jean-Ruel, Hubert; Godin, Michel; Pelling, Andrew E. (Frontiers in Physics, 2021)
Our organs and tissues are in constant motion, exposing epithelial cells to mechanical stretch. How these external forces impact cellular morphology, organization and dynamics in healthy and diseased tissues is still being elucidated. Carcinoma, the most common type of cancer, develops in the sheets of cells forming the epithelium and lining our organs and cavities. It usually begins with the transformation of a single cell via the activation of oncogenes such as Ras. Here, we show in a model system how mechanical stretch in epithelial sheets results in a more invasive phenotype in transformed cells. Cyclic strain impedes the apical extrusion of RasV12 cells from the healthy monolayer and prevents the formation of strong circumferential belts of actin in RasV12 cells. Concurrently, strain also changes the metastatic phenotype of newly transformed cells by greatly promoting the formation of RasV12 protrusions, potentially making them harder to be eliminated from healthy tissues. We also show that RasV12 and wild type MDCK cells possess distinct sensitivity to strain. External forces remodel their actin cytoskeletons and adhesion complexes differently, resulting in a more invasive system dynamic. Our work demonstrates that the Rho-ROCK mechanotransduction pathway is involved in regulating a mechanically-induced switch to a more invasive phenotype. The insights gained in this study reveal that the complex dynamics at play in healthy and transformed epithelial cells is drastically different in a mechanically active microenvironment when compared to static conditions.